Illuminating Collagen: Exploring Triple Helix Formation with Fluorescence-Based Kinetics - Smith, Rachel Lane (My University, 2024)
Collagen mimicking peptides (CMPs) can be used to understand the properties of collagen, a vital protein in the human body. Synthesis of collagen chains with a naphthalimide fluorophore allows for monitoring triple helix folding kinetics via fluorescence spectroscopy. Here we address whether kinetic behavior of the CMP system changes when Pro-Hyp-Gly (POG) repeats are interrupted by a non-native fluorescent amino acid, and if the folding rate can be controlled. Results indicate that the (POG)7 core can be interrupted by a fluorophore and still show first-order folding rates (k=0.001 s-1). However, this is dependent on the location of the fluorophore.
Keywords: collagen; fluorescence; kinetics